Development of an empirical model for energy usage and machine maintainability: palm oil pressing - Abdul Aziz, Aisar Amiree (IRC, 2020)
Palm oil mill system is one of the essential production processes for producing crude palm oil. Its electricity consumption profoundly influences its cost, machine maintainability as well as its environmental impact. Hence, this research aims to develop, test and verify the relationship between the electricity consumption of the palm oil screw press machine and its maintainability as well as the environmental impact due to the machine condition. In the context of maintainability, the reliability of the palm oil screw press machine is calculated by utilizing Weibull distribution and Maximum Likelihood Estimation method. The energy consumption is measured with the measurement of the electric current in the pressing machine and the carbon emission is indirectly expressed in a norm established by the Climate Registry. Analysis of the model will show the proof that as the reduction in reliability of palm oil screw press machine, its energy consumption spikes.